Gastric cancer risk stratification and surveillance after Helicobacter pylori eradication: 2020 - Tan, Mimi C. (Gastrointest Endosc, 2019)
Gastric cancer remains one of the most common causes of cancer deaths worldwide. The best current option for reducing gastric cancer deaths is Helicobacter pylori eradication combined with risk assessment and surveillance programs for those deemed to be at high risk for gastric cancer so as to identify lesions at a stage amenable to curative therapy. In this issue, Nam et al(1) report a retrospective study of Helicobacter pylori eradication on gastric cancer incidence among 10,328 Korean adults undergoing health checkups including an H pylori test-and-treat program. With a median follow-up of time 5.5 years, they report that H pylori eradication resulted in a significant reduction of gastric cancer incidence in comparison with individuals with persistent infection (eg, hazard ratio [HR] 0.29). Additional important risk factors included atrophic gastritis, family history of gastric cancer, and possibly higher body mass index, which was significant in 1 model but not the other. They also noted that a low serum high-density lipoprotein (HDL) level was associated with a significant increased cancer risk (HR 2.67) when adjusted for low-density lipoprotein (LDL) level and use of lipid-lowering drug.